2011
DOI: 10.5539/ibr.v4n4p164
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship between the Big Five Personality Dimensions and Job Involvement in a Foreign Based Financial Institution in Penang

Abstract: The relationship between the Big Five Personality Dimensions and job involvement was examined with a sample of one hundred and five (105) sales/customer service staff of a foreign based banking/financial institution in the Northern Region of Malaysia. Hypotheses were tested by means of regression analysis. Results indicate that extroversion and agreeableness are positively related to job involvement. Emotional stability/neuroticism, conscientiousness and openness to experience did not show any significant rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 49 publications
2
21
1
3
Order By: Relevance
“…Some empirical findings from previous research has found a link between Job Involvement on OCB [18][19][20][21]. On the other hand, Job Involvement is also associated with Talent Management [22], Personality [23,24] and Grit [25]. This paper contributes in the analysis of the determinant of OCB, by placing Job Involvement as a mediating variable.…”
Section: Second Personality Mckenna and Horswill Argued Thatmentioning
confidence: 88%
See 1 more Smart Citation
“…Some empirical findings from previous research has found a link between Job Involvement on OCB [18][19][20][21]. On the other hand, Job Involvement is also associated with Talent Management [22], Personality [23,24] and Grit [25]. This paper contributes in the analysis of the determinant of OCB, by placing Job Involvement as a mediating variable.…”
Section: Second Personality Mckenna and Horswill Argued Thatmentioning
confidence: 88%
“…Placing Job Involvement as a mediator in the relationship of Talent Management, Personality and Grit to OCB, aims to provide a more realistic relationship and strengthen the influence of antecedent to OCB. There was a causal relationship between Job Involvement and OCB [19,20], Talent Management and Job Involvement [22], Personality and Job Involvement [23,24], Grit and Job Involvement [25]. Although it does not directly quantify the relationship between Grit and Job Involvement, Rimfeld et al concluded that Grit is very similar to Personality and influences academic achievement [36].…”
Section: E Job Involvement As a Mediating Variablementioning
confidence: 99%
“…In the opinion of Eswaran et al (2011), openness to experience has a positive relationship with job satisfaction and job performance. They further assert that openness to experience is a valid predictor of the training proficiency criterion across occupations as the individuals with openness trait are more insightful, caring, and innovative.…”
Section: Openness To Experiencementioning
confidence: 99%
“…The five-factor model of personality characteristics illustrates that the personality of a human being is composed of five self-determining aspects which provide a considerable and a comprehensive catalogue for reassessing and re-evaluating the differences in the personalities (Eswaran et al, 2011). McDougall (2016 generally classifies personality traits into five distinctive elements such as disposition, intellect, character, temper, and temperament.…”
Section: Job Satisfaction and Personality Traitsmentioning
confidence: 99%
“…Personalization attracted increased attention in many areas. So the need to predict personality traits increase over time mainly when several research has shown the link between personality traits and success in human relationship and practices [3] [6]. As an instance an introverted person is not interested naturally to make so much relation with others while an extrovert person do.…”
Section: Introductionmentioning
confidence: 99%